Availability modeling of a safe communication system for rolling stock applications - Fort, Ada; Bertocci, Francesco; Mugnaini, Marco; Vignoli, Valerio; Gaggii, Vittorio; Galasso, Alessandro; Pieralli, Moreno (2013 IEEE International Instrumentation and Measurement Technology Conference (I2MTC), 2013)
The concern related to the design of highly reliable communication structures used in applications where safety plays a crucial role has always been under the attention of researchers due to the complexity and importance of the topic. In this paper the authors study the availability of a communication system topology exploitable in rolling stock applications comparing results for two different physical implementations, and discuss the modeling techniques exploited. The optimization of the selected architecture in terms of both availability and safety is provided under qualitative and quantitative aspects. The proposed modeling approach seems to represent a good tradeoff between complexity and adherence of results to realty. The modeling technique solution illustrated in this paper, starting from a given architecture, faces the problem of getting the desired safety degree according to IEC61508 standard through some standard approach exploiting Markov state space. The paper firstly describes the problem outline, then, it analyzes the possible architectures fitting for the solution and then describes the use of the state space techniques to address the desired availability targets to get enough confidence on the desired system robustness to random failures still keeping the requested safety integrity levels.